A quantitative shRNA screen identifies ATP1A1 as a gene that regulates cytotoxicity by aurilide B - Shohei Takase; Rumi Kurokawa; Daisuke Arai; Kind Kanemoto Kanto; Tatsufumi Okino; Yoichi Nakao; Tetsuo Kushiro; Minoru Yoshida; Ken Matsumoto (Scientific Reports, 2017)
Abstract Genome-wide RNA interference (RNAi) with pooled and barcoded short-hairpin RNA (shRNA) libraries provides a powerful tool for identifying cellular components that are relevant to the modes/mechanisms of action (MoA) of bioactive compounds. shRNAs that affect cellular sensitivity to a given compound can be identified by deep sequencing of shRNA-specific barcodes. We used multiplex barcode sequencing technology by adding sample-specific index tags to PCR primers during sequence library preparation, enabling parallel analysis of multiple samples. An shRNA library screen with this system revealed that downregulation of ATP1A1, an α-subunit of Na+/K+ ATPase, conferred significant sensitivity to aurilide B, a natural marine product that induces mitochondria-mediated apoptosis. Combined treatment with ouabain which inhibits Na+/K+ ATPase by targeting α-subunits potentiated sensitivity to aurilide B, suggesting that ATP1A1 regulates mitochondria-mediated apoptosis. Our results indicate that multiplex sequencing facilitates the use of pooled shRNA library screening for the identification of combination drug therapy targets.